Judicial Trends on Juvenile Delinquency: Enhancing Community Engagement for Child Protection (Journal of Advances and Scholarly Researches in Allied Education, 2018)
“The Supreme Court needs to have concentrated the most on involving the community in the operations under the JJA. The JJA provided ample scope for involving voluntary social workers and organizations at various stages and bodies related to the JJS. The Supreme Court could have also ensured implementation of those provisions by asking the voluntary organizations to depute one of their workers for various activities under the JJA. A direction by the Supreme Court was not likely to be ignored by the voluntary organizations. In addition, the Supreme Court could have directed the creation of district level committees constituted by voluntary social workers or organizations to act as watchdogs of the children’s interest. It would have not only increased community participation but also worked as a measure of quality control, especially important in the case of children who themselves cannot raise a voice against deficient services.”